Pelatihan Pemanfaatan Limbah Padi Menjadi Arang Sekam untuk Menambah Pendapatan Petani - Filda Rahmiati; Grace Amin; Emilius German (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
One of the efforts to increase paddy farmers’ income is to reprocess the rice hull into husk charcoal which has many benefits both for agriculture and industry. The utilization of rice hull is still limited nowadays. For example, when the harvest is abundant, the husk pollute the environment especially during harvest in the rainy season. The main purpose of this community service activity is to conduct training on how to produce husk charcoal from rice hull. The participants were paddy farmers at Sukamaju Village, Tambelang Subdistrict, Bekasi District. The activities carried out were to socialize the benefits of husk charcoal and how to make husk charcoal from rice hull. The farmers were given simple tools for the process of burning rice hull into husk charcoal and were demonstrated directly how it works until the packaging process which is ready for sale. After the training, the farmers at Sukamaju Village, are expected to be able to recycle rice hull into something which has value for sale resulting in benefits in terms of economy, crop productivity, and environmental preservation.